Menilai transparansi dan akuntabilitas pengelolaan keuangan desa: Pembelajaran pada Pemerintah Desa Bangunjiwo - Wulaningrum, Puspita Dewi; Baktiani, Dina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study aims to evaluate the level of transparency and accountability used in the financial management of Bangunjiwo Village Government. Data were collected through documentation and interview techniques. Qualitative descriptive analysis and case studies are two approaches used in this study. Regulation of the Minister of Home Affairs (Permendagri) 2014 Number 113 is an in-depth analysis tool in this study. This Permendagri assesses village financial management procedures and Government Accounting Standards (SAP). SAP is used to analyze the implementation of Bangunjiwo village government financial reports. The results of the study indicate that the Regulation of the Minister of Home Affairs No. 113 of 2014 is almost fully implemented. In addition, notes on financial reports and village balance sheets are not available in the village financial report, indicating that the Bangunjiwo Village Government has not fully implemented Government Accounting Standards. However, good coordination from village officials, initiatives in building teamwork, and supervision from related agencies and the community have helped encourage more transparent and accountable financial management.